Impact of organizational characteristics on employees’ entrepreneurial orientation with mediating role of knowledge process capabilities and moderating role of psychological factors in the era of COVID-19 - Basheer, Muhammad Farhan; Sabir, Saeed Ahmad; Raoof, Rabeeya; Hameed, Waseem Ul; Jabeen, Saida (Frontiers in Psychology, 2022)
Purpose – The study aims to investigate the impact of organizational characteristics and knowledge process capabilities on the entrepreneurial orientation amongst the manufacturing industry employees in the Punjab province of Pakistan. Additionally, this study has examined the mediating role of knowledge process capabilities in the relationship between organizational characteristics and entrepreneurial orientation amongst those employees and the moderating effect of psychological factors on the relationship of organizational characteristics with entrepreneurial orientation. Design/methodology/approach – The study has employed the survey-based methodology and data is collected with the aid of self-administered questionnaires. This study utilized the Partial Least Squares Structural Equation Modelling (PLS-SEM) to establish the validity and reliability of the measurement model and test the relationships. The response rate of the current study is 64.66 percent. Findings – The study findings have shown mixed results as one of the organizational characteristics namely resource and time availability is an insignificant determinate of entrepreneurial orientation amongst the manufacturing industry employees in Punjab province of Pakistan. Whereas management support, rewards, work discretion, and knowledge process capabilities appear as significant determinates of employees’ entrepreneurial orientation. The results indicated that knowledge process capabilities have a mediating role in the relationship between organizational characteristics and employee entrepreneurial orientation. Moreover, psychological factors namely, propensity to take risk and Locus of control have a significant moderating role on the relationship of management support, rewards, and work discretion with employee entrepreneurial orientation. Practical implications – The empirical insights of study are valuable and precious for policymakers, managers in manufacturing sectors of developing countries, such as Pakistan, to enrich their work performance through understanding the impact of organizational characteristics and knowledge process capabilities on the entrepreneurial orientation with moderating role of psychological factors. Originality/value – Studies on the mediating impact of Knowledge process capabilities on the linkage between organizational characteristics and entrepreneurial orientation with the moderating role of psychological factors remain limited. This study is one of the earliest studies that investigate these inter-relationships.